MEKANISME PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL YANG DIGUNAKAN OLEH BURUH/PEKERJA DALAM MENYELESAIKAN PERSELISIHAN HUBUNGAN INDUSTRIAL (Studi Kasus di Serikat Buruh Sejahtera Indonesia SBSI 1992 Kota Surakarta) - Dinar Wicaksono dan Sandi Septiyani, Binar Setya Wicaksono (GEMA, 2015)
Industrial Relations is a system or service that consists of elements of Employers, employees and government elements based on the values of Pancasila and the 1945 Constitution of the Republic of Indonesia, (Article 1, Section 22 of the Manpower Act). Implementation of Industrial Relations are arranged in the form of provisions, both normative provisions and the provisions of existing law. Industrial Dispute, a condition in which the presence of dissent that resulted in a conflict of interests between employers and employees because of the dispute over the rights, interests, Termination of Employment ("layoffs") or a cooperation agreement. SBSI (Indonesian Prosperity Trade Union) in 1992 Surakarta City is one of the unions / workers who focus on accomplishing clash industrial relations experienced by its members either by taking judicial and non-legal options